Human Attitude and Technology: Analyzing a Legal Culture on Electronic Court System in Indonesia (Case of Religious Court) - Latifiani, Dian (JILS (Journal of Indonesian Legal Studies), 2021)
The use of technology for the judiciary is now a necessity. In Indonesia, information technology is used for court administration to achieve fast, simple, and low-cost trials. The Supreme Court issued a Supreme Court Regulation as the legal basis for the administration of administration and electronic trials. This is done to make it easier for people to seek justice. The electronic court began in 2018. Its implementation is carried out in stages, starting with certain religious courts as an introduction. Subsequently carried out for all Religious Courts in Indonesia. The problems of this study are: (i) the condition of the religious court from the perspective of legal culture, (ii) reforming the religious court in the perspective of legal culture, (iii) renewing the legal culture of religious courts using an electronic system / E court. The social setting is the Office of PA Kendal class 1 A and PA Pemalang Class 1 A. The study shows; (i) The reality of the number of case registrations in 2019 at the Kendal Religious Court Class 1A shows that the legal culture of registering using the E-Court is 117 cases (3.4%) whereas 5 cases litigation (0.13%). The reality of the legal culture of case registration at the Pemalang Religious Court Class 1A with E Court totaling 94 cases (1.8%). Whereas the legal culture of the trial by e-litigation at the Pemalang Religious Court since the issuance of Perma 1 of 2019 has only 4 cases (0.1%), (ii) the development of legal culture in the electronic system of religious courts is carried out by developing an internal and external legal culture in terms of pre-registration, court administration, trial. Development of an internal legal culture for judges, e-court operator officers, e-court corner officers, public service officers to invite justice seekers to use e-court in its resolution. The service officer also helps justice seekers to make an email as an electronic domicile as a requirement for e-court registration. Development of an external legal culture through socialization. Socialization for advocates is carried out through media meetings, flyers, and online web media. As well as mandatory online / e-court registration. Development of external culture for the community (other users) at the village level in the jurisdiction of the local religious court. The effort is to work at the village level to conduct socialization about electronic courts in the village by the Religious Courts.